Analisis Framing Pan dan Kosicki mengenai Pro Kontra Deforestasi Hutan di Indonesia dalam Bingkai Media Daring Tempo.co dan Detik.com - M. Abdi Octavianus; Doddy Iskandar (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. At the end of 2021, the audience in Indonesia was enlivened by a “tweet” from the Minister of Environment and Forestry Siti Nurbaya posted on her Twitter account.